EVALUASI SUSU SEGAR MENGGUNAKAN LIFE CYCLE ASSESSMENT (LCA) DAN ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PENERAPAN GREEN SUPPLY CHAIN €‹ €‹MANAGEMENT - Tia Haryanti; Rossi Septy Wahyuni (Jurusan Kimia FMIPA Universitas Lampung, 2024)
This study aims to evaluate the impact of waste on the environment in fresh milk production activities. Fresh milk supply chain activities start from dairy farming activities to the distribution process of fresh milk to the fresh milk processing industry. This study aims to identify the most significant potential of fresh milk production activities on the environment, as well as provide improvement alternatives based on the most significant environmental impacts caused by fresh milk production activities. This research was conducted in a dairy farming cooperative which is an organization that produces fresh milk, namely Karya Nugraha Jaya Producer Cooperative Kuningan. Evaluation of the environmental impact of fresh milk production activities using the Life Cycle Assessment (LCA) method. The analysis was conducted using SimaPro 9.5 software. Based on the results of the LCA, it is known that the fresh milk extraction activities that occur on the farm have the highest impact contribution of 3.57E3 Pt. Proposed improvements are given based on fresh milk extraction activities using the Analytical Hierarchy Process approach. The proposed improvement alternatives were analyzed using the pairwise comparison method to determine the highest weight. The Installation of Wastewater Treatment (IPAL) was recommended as a prioritized improvement with a total value of 0.48963.